Netherton syndrome plus atopic dermatitis: Two new genetic mutations in the same patient. Issue 11 (25th November 2021) - Moar, Agata; Bruni, Manfredo; Schena, Donatella; Rigotti, Erika; Colato, Chiara; Novelli, Antonio; Cesario, Claudia; Girolomoni, Giampiero
Abstract: A child who comes to our attention for the appearance of erythematous, scaly lesions localized to the upper and lower limbs for 2 months. Histological features suggested ichthyosiform disease and concomitant mutations in the SPINK5 and FLG2 genes confirmed Netherton syndrome with severe atopic manifestations. Abstract : Our case is particularly interesting because it clearly highlights the clinical characteristics of a rare disease whose atopic manifestations have been aggravated by a concurrence of FLG2 and SPINK5 mutations. Furthermore, trichoscopy showing invaginated trichoresis could suggest an early diagnosis of Netherton syndrome.